Machinery Changes and Challenges of Architecture and Landscape Design in the Virtual Reality Perspective. (17th April 2023) - Jin, He; Zhang, Nan
Abstract : With the in-depth study of architectural planning in China, more and more designers and developers are aware of the superiority of the use of technological robots to improve the speed and quality of construction, weakening past experience and based on real-world research through modern technology. However, the application of this method in the predesign work is not mature. To be specific, designers may lack expertise due to the overly detailed division of labor. In addition, the developer's blind pursuit of profitability leads to inaccurate market positioning and forecasting. At the same time, the lack of effective communication between designers and developers, architects and owners makes the predesign work ineffective and does not provide reasonable and accurate guidance for the building design. Therefore, the predesign work requires the designer to analyze and select the site reasonably. In addition, it is necessary to conduct in-depth research on the target customers. At the same time, it is necessary to accurately position and predict the dynamic market, and then to have a thorough understanding of the norms and regulations. As a result, the predesign work enables the design to be analyzed in the context of the actual situation. Then, according to the data and information from various aspects, effective planning and argumentation are carried out, and corresponding decisions are made to provide guidance for the design. Overall, predesign is a process of rational planning of the design process. In fact, in the process of landscape design innovation, it is necessary to fully consider the requirements of the intelligent era. Therefore, multimedia and advanced robotics can continuously enhance the interaction and experience of urban landscape to make it integrate into the intelligent system of the future city. In other words, multimedia technology can enhance the new image of the city in an intelligent, digital, and humanized interactive experience. Especially in the landscape design process, the advent of computers has enabled landscape designers to use relevant design software to design their own works, thus giving them unlimited design possibilities. Virtual reality technology, as a form of computer technology, provides designers with a new creative experience in the design phase of a landscape project. To be specific, this technology allows designers to freely grasp the design space and scientifically compare the differences between design options to make the design more reasonable and complete. Therefore, this paper analyzes the differences in the general environment and concepts of 3D software virtual reality technology, starting from the characteristics of the application of 3D technology as an entry point. At the same time, this study uses the similarities and differences in technology to discover the vital role of using virtual reality technology to reconstruct the space and the impact of robots on modern architecture.